Launch and Training – The Food Security Simulator Ethiopia (FSSE) - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
On January 22, 2025, the Food Security Simulator Ethiopia (FSSE) was officially launched at the International Livestock Research Institute (ILRI) Campus in Addis Ababa. The event commenced with an opening remark by Alemayehu Seyoum Taffesse (DPhil), a Senior Research Fellow and Program Leader of the International Food Policy Research Institute (IFPRI) - Ethiopia Office. This was followed by a speech from Dr. Getachew Diriba, Senior Advisor and Principal Coordinator, Ethiopian Food Systems Transformation, Office of the Minister, Minister of Agriculture, who highlighted the significance of FSSE in addressing Ethiopia’s food security challenges.